AB0557 Assessing the sexual impact of rheumatic disease in spondyloarthritis patients – where do we stand?. (23rd January 2014) - Aguiar, R.; Ambrósio, C.; Cunha, I.; Barcelos, A.
Abstract : Background: The impact of rheumatic diseases on patients' sexuality has been, for a long time, an ignored topic. As quality of life in these patients became more valorized, sexuality, as a major aspect for the individual's well being, arised as a subject to be considered over the last decade 1 . The awareness of the physicians for the problem is of great importance, since the impact in sexual life might be a major concern and still, a quite uncomfortable topic for the patient – both with healthcare professionals and partners. Objectives: To analyze the approach by the healthcare service and/or partners on the patients' perspective of the impact of the rheumatic disease in their sexual activity. Methods: An anonymous questionnaire was performed, consisting in demographic data (sex, age, disease duration, civil status, professional status and educational level), and questions related to the importance attributed to sexual activity, as well as to the approach of the topic by the patient and healthcare professionals, with multiple choice questions and questions to be answered through a visual analogical scale. A descriptive study was performed. Results: 95 patients with the diagnosis of spondyloarthritis were enrolled and 76 answered the questionnaire; 31 had psoriatic arthritis, 30 had ankylosing spondylitis, 9 had undifferentiated spondyloarthritis and 6 had inflammatory bowel disease spondyloarthritis; 40 were male, 35 were female and 1 unknown. Mean age was 46.08±12.08 and mean disease duration was 12.17±10.32 years. Most of patients were married (56) or common law married (8); 19 patients had completed primary school only and less than one quarter were graduate or higher. In a visual analogical scale, mean importance give to sexual capacity was 74.67±24.55. Among the 76 patients, only 35 stated they talked about the subject with their partner; however, the great majority (66 patients) said they had the partner's understanding towards their limitations in sexual activity. The perception of conditioning in the conjugal relationship was, in a visual analogical scale, 33.68±31.56. 58 patients had never talked about it with anyone else and 65 had never been questioned by any health professional (rheumatologist, general practitioner or nurse). Conclusions: This work emphasizes that the impact of spondyloarthritis on sexual activity is a topic rarely approached either by the patients, either by health professionals. Since patients valorize a lot their sexual capacity and seem not to talk about the limitations imposed by their disease, this subject might deserve a greater attention, including from rheumatologists and other healthcare professionals. References: Helland Y, Kjeken I, Steen E, Kvien TK, Hauge MI, Dafinrud H. Rheumatic Diseases and Sexuality: Disease Impact and Self-Management Strategies. Arthritis Care & Res 2011;5:743–750 Disclosure of Interest: None Declared